Aḥmad Ibn ʿUjayl and Bayt al-Faqīh: the birth of a sacred site - Mochtari de Pierrepont, Zacharie (Proceedings of the Seminar for Arabian Studies, 2014)
Between the second half of the sixth/twelfth and the late ninth/fifteenth centuries (AH/AD), the mention of scholars in the written sources increased sharply in Yemen, as is shown by the blossoming of local biographical dictionaries during that period. This literature coincides with the dissemination of sacred places in Lower Yemen, supported by the construction of shrines and by the pious visits to the tombs of saints and their descendants. One man symbolizes the astonishing success of these lineages, the faqih Ahmad b. ʿUjayl (d. 690/1291) in central Tihāma. Our purpose is to investigate the reasons that led to the rise of this figure and his families. The rise of the Banū ʿUjayl lineage seems to link the construction of new forms of social and moral authority with ambitious territorial strategies. We will address these issues through various Yemeni Arabic sources, which include biographical and hagiographie literature, historical chronicles, administrative records, and architectural and archaeological data.